1998
DOI: 10.1016/s1074-7613(00)80552-x
|View full text |Cite
|
Sign up to set email alerts
|

A Poxvirus-Encoded Semaphorin Induces Cytokine Production from Monocytes and Binds to a Novel Cellular Semaphorin Receptor, VESPR

Abstract: The vaccinia virus A39R protein is a member of the semaphorin family. A39R.Fc protein was used to affinity purify an A39R receptor from a human B cell line. Tandem mass spectrometry of receptor peptides yielded partial amino acid sequences that allowed the identification of corresponding cDNA clones. Sequence analysis of this receptor indicated that it is a novel member of the plexin family and identified a semaphorin-like domain within this family, thus suggesting an evolutionary relationship between receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
178
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(182 citation statements)
references
References 46 publications
(21 reference statements)
3
178
0
1
Order By: Relevance
“…In particular, Plexin C1 is expressed on DC and neutrophils (Walzer et al, in press). Plexin C1 was shown to be the cellular receptor for the poxvirus semaphorin A39R [11]. Our previous results showed that, as in neurons, Plexin C1 engagement by A39R semaphorin on mouse DC induces local actin cytoskeleton rearrangement and inhibits integrin-mediated adhesion (Walzer et al, in press).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In particular, Plexin C1 is expressed on DC and neutrophils (Walzer et al, in press). Plexin C1 was shown to be the cellular receptor for the poxvirus semaphorin A39R [11]. Our previous results showed that, as in neurons, Plexin C1 engagement by A39R semaphorin on mouse DC induces local actin cytoskeleton rearrangement and inhibits integrin-mediated adhesion (Walzer et al, in press).…”
Section: Introductionmentioning
confidence: 90%
“…All of the experimental procedures used in this study were approved by a local committee according to federal guidelines. SFHA39R (Shorty-Flag-Histidine, referred as A39R in the text) was expressed in Chinese hamster ovary (CHO) cells and purified as previously described [11]. All proteins were tested for endotoxin content using a Limulus assay (Whittaker M. A. Bioproducts, Walkersville, MD) and were shown to be <3 endotoxin units/mg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both were found to bind to plexin-C1. 20,84 However, recent data suggest that in the nervous system integrins and in particular those containing the b1 subunit, are functional receptors for Sema7A. 85 A possible function of SEMA7A in cancer is unknown.…”
Section: Classmentioning
confidence: 99%
“…Plexins form a large family of transmembrane proteins, members of which function as co-receptors for both secreted and membrane-associated semaphorins (Fujisawa, 2004;Puschel, 2002;Tamagnone and Comoglio, 2000). Semaphorins bind either directly to plexins or activate plexin-dependent signaling by associating with ligandbinding subunits such as neuropilin proteins (Comeau et al, 1998;Rohm et al, 2000;Takahashi et al, 1999;Tamagnone et al, 1999;Winberg et al, 1998). Following ligand engagement, the plexin cytoplasmic region activates poorly understood downstream signaling pathways, leading to modifications of the growth cone cytoskeleton and axon repulsion (Pasterkamp, 2005;Pasterkamp and Kolodkin, 2003).…”
Section: Introductionmentioning
confidence: 99%